COMPARATIVE ANALYSIS O F ANALYTICAL AND NUMERICAL SOLVING OF HEAT PROBLEM, WHICH USES THE HEAT CONDUCTION EQUATION - A. N. Chichko; O. A. Sachek; A. V. Borozdin (Литьë и металлургия, 2007)
The numerical analysis of temperature field, being cooled under analytical and numerical schematic models, is carried out. It is shown that implicit schematic model is close to analytical decision.